Analysis of Differential Diagnosis of Benign and Malignant Partially Cystic Thyroid Nodules Based on Ultrasound Characterization With a TIRADS Grade-4a or Higher Nodules - Wang, Chen-Yi; Li, Yang; Zhang, Meng-Meng; Yu, Zhi-Long; Wu, Zi-Zhen; Li, Chen; Zhang, Dong-Chen; Ye, Ying-Jiang; Wang, Shan; Jiang, Ke-Wei (Frontiers in Endocrinology, 2022)
Partially cystic thyroid nodules (PCTNs) are a kind of thyroid nodule with both solid and cystic components, and are usually misdiagnosed as benign nodules. The objective of this study was to determine the ultrasound (US) characterizations with a TIRADS Grade-4a or higher partially cystic thyroid nodules (PCTNs) which are associated with being malignant or benign. In this study, 133 PCTNs with a TIRADS Grade-4a or higher were enrolled; 83 were malignant and 50 were benign. TI-RADS classification can detect malignant PCTNs, and its sensitivity, specificity, positive predictive value, negative predictive value, and accuracy are 39.8%, 96.0%, 94.3%, 49.0%, and 60.9%, respectively. Univariate analyses revealed that nodule shape, margin, and structure were related to PCTNs’ being benign and malignant, among which nodules taller-than-wide, with an irregular shape, non-smooth margin, eccentric sharp angle, or edge sharp angle were significantly associated with malignancy while ovoid to round nodules, smooth margins, multiple separation, and eccentric obtuse angle structures were significantly associated with a benign nature. For the solid part of PCTNs, its free margin, echo, and calcification are related to benign and malignant PCTNs. Among them, the free margin of the solid part is non-smooth, hypoechoic, and microcalcification, which are related to malignant PCTNs, while the free margin of the solid part is smooth, isoechoic, macrocalcification, non-calcification and are related to benign PCTNs. Calcification of solid part and free margin are important factors for predicting malignant PCTNs. In addition, nodules’ composition, blood flow signal, and other factors had nothing to do with PCTNs’ being benign or malignant. In the multivariate Logistic regression analysis, solid part calcification (OR: 17.28; 95%CI: 5.14 58.08) and free margin (OR: 3.18; 95%CI: 1.01 10.00) were revealed to be the strongest independent predictors for malignancy (P<0.05). Our study indicated that understanding the ultrasound characteristics of malignant PCTNs, to avoid misdiagnosed PCTNs patients, is important to make a precise diagnosis and prognosis of PCTNs.